A finite element analysis of the intra-abdominal pressure and paraspinal muscle compartment pressure interaction through the thoracolumbar fascia. Issue 10 (26th July 2020) - El-Monajjed, Khaled; Driscoll, Mark
Abstract: Thoracolumbar fascia involvement is often neglected when studying the biomechanics of the spine. The purpose of this study was to develop, validate, and explore the use of a novel finite element model of the spine, inclusive of the Thoracolumbar Fascia, Paraspinal Muscular Compartment (PMC) and the Intra-Abdominal Pressure (IAP) based on published clinical studies. Reaction forces were acquired at five critical anatomical locations. Results showed that elevated IAP decreased the posterior force and balanced the anterior forces when PMC pressure was asymmetric. This novel finite element study demonstrated a link between the TLF compartments supporting its involvement in spinal stability.